India Economic Road Map: The Next Five Years 2002-2007 The Essence - Planning Commission (Planning Commission Government of India, 2002)
The Tenth Five-Year Plan of India (2002–2007) presents a comprehensive roadmap to achieve sustained economic growth, social equity, and inclusive development. With ambitious targets including an 8% GDP growth rate, doubling per capita income, and generating one crore employment opportunities annually, the Plan emphasizes governance reforms, decentralization, and enhanced private sector participation. Key sectors targeted include agriculture, manufacturing, infrastructure, and science and technology, alongside proactive disaster management and fiscal reform. Social development measures focus on poverty alleviation, education, healthcare, rural development, and empowerment of marginalized communities. The Plan outlines structural reforms, investment promotion, and policy measures designed to ensure sustainable growth, improve living standards, and strengthen India’s position as a globally competitive economy.
Planning Commission Government of India New Delhi
Keywords: Economic Growth; Employment Generation; Poverty Alleviation; Governance Reform; Infrastructure Development; Agricultural Productivity; Manufacturing Sector; Disaster Management; Science And Technology; Foreign Direct Investment; Social Justice; Rural Development